Os multiletramentos no chão da escola: desafiando realidade - SANTOS, Érica Emmanuelle Lima (Universidade Federal do Pará, 2019)
This dissertation assumes that the use of technology is a great attraction for young people and adolescents, from the belief that technological resources could be allied in the implementation of pedagogical practices more connected to the reality of the student and the urgency to promote digital inclusion and Multilearning of students, in view of the needs of contemporary society. In order to put it into practice, we started with the following problems: How can TDIC be used as an instrument in the teaching-learning process, contributing to the critical and reflexive reading and multilearning of students? In order to answer such questioning, a proposal for intervention was developed, with a focus on reading, from the conception of Project of Reading and writing of discursive genres, by Lopes-Rossi (2008), from the perspective of Pedagogy of Multiletraces. The activities of reading were based on the dialogical conception of language, according to the Bakhtinian perspective, from the discursive advertising genre and sought to confirm / deny two hypotheses: a) Although they are digital natives, students do not master the resources derived from multimodal texts , Nor the reading of implicit, leading in a superficial reading, which - in the practice of the genre in question, allows the dissemination of prejudices and unhealthy consumer relations; B) The use of social networking sites (SRS) in hybrid learning environments is a facilitator in the teaching-learning process, because it brings the teacher closer to the context of the student, and promotes the re-signification of these spaces. It was defined as a general objective to use the TDIC, and in particular the SRS Facebook, as teaching-learning tools, in order to develop critical and reflexive reading, as well as to contribute to the multiletracy of the students. The specific objectives listed were a) To use the TDIC as teaching-learning tools, in order to contribute to the multilearning of the students, as well as to make them reflect on the power of the publicity and its discourse; B) To promote the reflexive reading, providing linguistic instruments necessary for the realization of the inferences and reading the implicit ones; C) To instrument students in the use of technological resources necessary for the multiletracy practices carried out. The application of this project began in the second half of 2016 and ended in the second half of 2017, having as students in the 9th year of elementary school a school that was part of the state network in the city of Belém-Pa. The theoretical basis was based on Bakhtin (2003), regarding the discussion of the discursive genres, Cope, Kalazantis (2000), Coscarelli (2007), Rojo (2012) regarding multiletramentos, Knoll (2012), Sandmann (2003) in relation to advertising, advertising and advertising, among others. The research was ethnographic, followed the methodology of participant observation and was of an applied nature and demonstrated that the use of TDICs favors the critical reading of multimodal texts, but that the use of SRS as a pedagogical tool requires a greater involvement between teacher / student in order for the learner to engage and see the instrument beyond entertainment.